ГЕРМЕНЕВТИЧНА ІНТЕРПРЕТАЦІЯ ЯК ПОРЯДОК ДИСКУРСУ - Дубініна Віра Олександрівна (International Journal of Innovative Technologies in Social Science, 2020)
The modern philosophical hermeneutics is considered in the context of ideas about the transformation of discursive practices and their influence on the formation of philosophical theories. Hermeneutics as a theory of understanding and interpretation itself acts as a family of discursive strategies, conditionally combined into a single whole and representing a new type of communication with the primary source of philosophical knowledge, which is especially important for understanding its individual components. The relationship of philosophical hermeneutics with the philosophy of language and the theoretical uncertainty of the most important elements of hermeneutic discourse are shown. In this article, we combine the idea of philosophical hermeneutics, as it developed in German philosophy of the XIX-XX centuries. with the notion that every philosophical theory, not to mention philosophical directions, develops, establishes a new, own order of discourse and that it is philosophical hermeneutics that is this new order that is somehow present in all directions of twentieth-century philosophy without exception: phenomenology, analytical philosophy, Marxism, psychoanalysis, etc. This interpretive discourse penetrates the flesh and blood of modern philosophy, being its quintessence and main motive.One can imagine the space of interpretation as a certain common space of the collective unconscious in which each interpreter, as a dreamer, moves along its own path, i.e. this interpreter’s dream is something larger, larger than what each of us sees in a dream. Then the figure of the coordinator, meta- interpreter, moderator, standing above individual interpretations, arises or becomes in demand.For all its ambiguity and vagueness of its theoretical foundations, philosophical hermeneutics undoubtedly seeks to constitute itself as a discursive norm, absorbing and subjugating all other speech practices. This allows us to talk about the hermeneutic paradigm of modern philosophy, the ideal of discourse, developing since antiquity and finding its embodiment and resolution in a wide range of modern philosophical theories. In a certain sense, one can speak of hermeneutics as a specific agent that penetrates into the very depths of interpretation schemes and methodologies. Perhaps this position of hermeneutics may cause criticism and suspicions of inescapable totality and peculiar repressiveness if the very nature of hermeneutic discourse did not contradict this point of view. Hermeneutics, by definition, opposes any violence against interpreted material, striving to reflect the whole spectrum of possible meanings and definitions.